Inelastic neutron scattering applied to the investigation of collective excitations in topologically disordered matter - Suck, J.-B. (Condensed Matter Physics, 2008)
Inelastic neutron scattering techniques are introduced here as one of the most important experimental techniques in the investigation of collective excitations in fluids (liquids and compressed gases) and amorphous solids. The correlation functions involved, the spectra of which are determined in inelastic neutron scattering experiments, the dispersion relations of the collective excitations and how they are obtained from the measured spectra and finally two of the most often used instrumental techniques are briefly discussed.